A technique to reduce arms fatigue on intradialytic - Isnaini, Nur; Kusumantri, Megarini (Universitas Muhammadiyah Purwokerto, 2021)
Background: The hemodialysis process that takes 4 to 5 hours may lead to various problems, including arms' fatigue on the forearm with attached Cimino access. A technique is required to overcome this fatigue.Technique: By using a supportive hand pillow made by adjusting the position of the elbow and the length of the arm. The pillow is placed under the patient's forearm with Cimino access. Trial usage of this pillow was conducted on two persons for two cycles of hemodialysis. Both stated that arm fatigue was reduced and more comfortable.Conclusion: Using hand pillows for hemodialysis patients is favorably beneficial to reduce forearm fatigue during the Intradialytic phase.